Simple and Low-Cost Oil/Water Separation Based on the Underwater Superoleophobicity of the Existing Materials in Our Life or Nature - Bian, Hao; Yong, Jiale; Yang, Qing; Hou, Xun; Chen, Feng (Frontiers in Chemistry, 2020)
The achievement of high-efficiency oil/water separation has huge implications for protecting environment and reducing economic losses, but there is still a great challenge. Currently, most artificial oil/water separating materials are fabricated through complex preparation process, resulting in the very high cost of separation. In this paper, we present a simple and low-cost method to achieve oil/water separation by using the underwater superoleophobic materials that already exist in our life or nature. Taking filter paper and zeolite layer as examples, we show the inherent porous microstructures of these materials. Such porous microstructures endow filter paper and zeolite layer with strong ability to absorb water and the underwater superoleophobicity. Based on the porous feature and underwater superoleophobicity, the pre-wetted filter paper and zeolite layer can be used to effectively separate the mixture of water and oil, with great separation capacity. The existing materials (e.g., filter paper and zeolite layer) with both porous microstructure and underwater superoleophobicity in our life or nature are green and low-cost, and can be easily obtained. Such advantages allow those materials to potentially solve the pollution problems caused by the discharge of industrial oily wastewater and the oil-spill accidents.